THE PROBLEM OF UPBRINGING AND FORMATION OF CONSCIOUSNESS AND THINKING OF YOUTH (Scientific journal of the Fergana State University, 2023)
In this article, the purpose of the research is to define the meaning and quality of all relations in society, to form and educate young people's consciousness in a noble movement, such as creating the foundations of the Third Renaissance. For this, it was also studied that the functional fragmentation and declarative nature of the institutional system is an obstacle to achieving the expected results. It is social that in the application of genetic discoveries in medicine, the criteria of humanity, morality, environmental protection, determination of a stable ecological situation, preservation of the purity of the natural environment, rational use of transnational and natural resources, and sustainable ecological security philosophically based.